(6b-4)(b-8)=0

Simple and best practice solution for (6b-4)(b-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6b-4)(b-8)=0 equation:


Simplifying
(6b + -4)(b + -8) = 0

Reorder the terms:
(-4 + 6b)(b + -8) = 0

Reorder the terms:
(-4 + 6b)(-8 + b) = 0

Multiply (-4 + 6b) * (-8 + b)
(-4(-8 + b) + 6b * (-8 + b)) = 0
((-8 * -4 + b * -4) + 6b * (-8 + b)) = 0
((32 + -4b) + 6b * (-8 + b)) = 0
(32 + -4b + (-8 * 6b + b * 6b)) = 0
(32 + -4b + (-48b + 6b2)) = 0

Combine like terms: -4b + -48b = -52b
(32 + -52b + 6b2) = 0

Solving
32 + -52b + 6b2 = 0

Solving for variable 'b'.

Factor out the Greatest Common Factor (GCF), '2'.
2(16 + -26b + 3b2) = 0

Factor a trinomial.
2((2 + -3b)(8 + -1b)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(2 + -3b)' equal to zero and attempt to solve: Simplifying 2 + -3b = 0 Solving 2 + -3b = 0 Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3b = 0 + -2 -3b = 0 + -2 Combine like terms: 0 + -2 = -2 -3b = -2 Divide each side by '-3'. b = 0.6666666667 Simplifying b = 0.6666666667

Subproblem 2

Set the factor '(8 + -1b)' equal to zero and attempt to solve: Simplifying 8 + -1b = 0 Solving 8 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1b = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1b = 0 + -8 -1b = 0 + -8 Combine like terms: 0 + -8 = -8 -1b = -8 Divide each side by '-1'. b = 8 Simplifying b = 8

Solution

b = {0.6666666667, 8}

See similar equations:

| x^2+101=1 | | -1.5x+.5=.66 | | 4(2x+9)-12-2x=20 | | x^2+65=1 | | 9-[-2b+8]=2.8 | | 2n+2.1=4.3 | | 8-6n=-2n | | .50(30x+10)-6(x-2)=28 | | 15X-7Y=1 | | 4a+2b+(-1-a-b)=-11 | | 64x-56=-8y | | X^2+16x+75=0 | | (4o-28)+(o+13)=90 | | X^2+12x+36=81 | | 21x^2=34x+55 | | Y=-16t^2+254 | | 1.6=.83x | | 2n-3=8n+9 | | 7x=90+22 | | (4x+18)=(16x-12) | | 18-2(4x-1)=12 | | (4t+16)+(5t-21)=180 | | 7+2(3x-1)=8x-3(2x+5) | | -3x-2y=17 | | y-32=-10 | | p^2-2pq+q^2=0 | | x^2-6x^2-9= | | 30-6x=6-3x | | Y=X^2+9x+18 | | -16x^2-60x+6=0 | | x^2+16x-78=0 | | 18s^3=-50s |

Equations solver categories